(untitled) (International conference on multidisciplinary science, 2026)
This article examines the theoretical and practical foundations of working with electronic spreadsheets. It analyzes the role of spreadsheets in the educational process, their functional capabilities, and their importance in developing students’ analytical thinking skills. Methods of data processing, analysis, and visualization using modern software tools are also discussed. The research results demonstrate that effective use of spreadsheets improves the quality of education.